2017
DOI: 10.5964/jspp.v5i2.721
|View full text |Cite
|
Sign up to set email alerts
|

Gender biases and linguistic sexism in political communication: A comparison of press news about men and women Italian ministers

Abstract: This research on press communication uses a synchronic perspective concerning eighteen ministers, balanced by gender, in the Renzi government (in 2014), as well as a diachronic perspective concerning women ministers from five governments (from 2006-2014). The governments in 2014 and of 2013 were predominantly center-left, with the participation of center and center-right parties, whereas the previous governments had technical-professional rather than political ministers (in 2011), center-right (in 2008), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 60 publications
(75 reference statements)
0
3
0
2
Order By: Relevance
“…Consequently, the findings of this research cannot be generalized to assert that the process linking individuals with a high need for cognitive closure to prejudiced attitudes through implicit person theories functions in an identical manner across different societies and cultures. It is important to acknowledge that past research has shown a consistent tendency to view women as unsuitable for positions of authority, and there is no indication that this effect is limited to a specific culture; rather, it appears to be a global phenomenon [52,53]. Nevertheless, future research should aim to establish that prejudice toward women in leadership roles is a universally endorsed phenomenon by examining this crucial hypothesis in samples from diverse cultural backgrounds.…”
Section: Limits and Future Directionsmentioning
confidence: 99%
“…Consequently, the findings of this research cannot be generalized to assert that the process linking individuals with a high need for cognitive closure to prejudiced attitudes through implicit person theories functions in an identical manner across different societies and cultures. It is important to acknowledge that past research has shown a consistent tendency to view women as unsuitable for positions of authority, and there is no indication that this effect is limited to a specific culture; rather, it appears to be a global phenomenon [52,53]. Nevertheless, future research should aim to establish that prejudice toward women in leadership roles is a universally endorsed phenomenon by examining this crucial hypothesis in samples from diverse cultural backgrounds.…”
Section: Limits and Future Directionsmentioning
confidence: 99%
“…Относительно подробную программу представила «Лига», где внимание уделялось не только снижению налогового бремени семей, но и упоминались трудовые права женщин вообще ( 5), а также предлагались идеи для достижения равенства в правах и возможностях женщин и мужчин (3). Как и в случае с правыми политическими партиями Германии, наиболее часто упоминаемый фрейм -это «семья» (7), где направлениями были традиционные семейные ценности, брачный возраст, брак, благополучие семьи. «Братья Италии» используют гендерную тематику главным образом для того, чтобы подчеркнуть свою приверженность традиционным итальянским ценностям, поэтому в программе есть упоминания семьи (7), матерей (1), насилия в отношении женщин (1), меньшинств (1).…”
Section: результатыunclassified
“…Как и в случае с правыми политическими партиями Германии, наиболее часто упоминаемый фрейм -это «семья» (7), где направлениями были традиционные семейные ценности, брачный возраст, брак, благополучие семьи. «Братья Италии» используют гендерную тематику главным образом для того, чтобы подчеркнуть свою приверженность традиционным итальянским ценностям, поэтому в программе есть упоминания семьи (7), матерей (1), насилия в отношении женщин (1), меньшинств (1). Наконец, партия Сильвио Берлускони «Вперед, Италия» практически не поднимает вопросы гендерного равенства в своей предвыборной программе, но упоминает о женщинах, когда сообщает о планах Немецкие партии акцентируют внимание на уже реализуемых программах для достижения равных возможностей мужчин и женщин, в то время как итальянцы говорят о необходимости изменений в законодательстве для инициации работы по обеспечению равных прав.…”
Section: результатыunclassified
“…Female politicians have been reported to receive fewer quotes (Ross and Comrie, 2012; Semetko and Boomgaarden, 2007; Vos, 2013) and more visual depictions (Humprecht and Esser, 2017; Wagner et al, 2017), although a number of other studies do not support these findings (Goodyear-Grant, 2013; Wagner, 2014). Likewise, studies have reported mixed findings on more extensive measures of news prominence; for example, whether a politician is named first in the story, named multiple times or named in a headline (Sensales and Areni, 2017; Trimble, 2007; Wagner et al, 2017).…”
Section: Women Politicians In News Coveragementioning
confidence: 99%